Empirical Analysis of the Socio-Economic Influence of Sports Betting on Academic Performance of Students in Nigerian Tertiary Institutions - Adewole, Ayoade Iyabode; Adeogun, Adedayo Ayodeji (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2025)
The study investigated the socio economic and psychological drivers behind the effect of sport betting on academic performance in tertiary institution using descriptive analysis and multinomial logistic regression model. Descriptive survey design was adopted utilizing simple random sampling method in choosing students from the targeted population. The study's findings revealed that academic performance was affected significantly by demographic statistics (age and sex), influence of loss of dignity, peer influence, hobby, immoral act and unnecessary additions. Additionally, there was no significant effect of religious belief and entertainment towards sport betting influencing academic performance among tertiary institutions student. Consequently, suggestions on how to mitigate identified significant predictors that influence academic performance of students via sport betting and strategies for interventions to reduce the mayhems in educational institutions were given.